Information Literacy and Lifelong Learning: Policy Issues, the Workplace, Health and Public Libraries - Crawford, John; Irving, Christine (Chandos information professional series, 2013)
This book reviews the role of information literacy (IL) in developing employability skills, personal health management and informal learning from a variety of areas including: information policy issues, information usage and training needs and skills development. Early years education, lifelong learning and the role of IL in relevant organisations, including government departments, skills agencies, and professional bodies will also be considered. With a UK focus, this book also considers the leading role of the US in the development of information literacy policy. Case studies and examples of good practise are included and discussed, drawn primarily from Europe, North America and Australasia, also identified examples from other countries. Looks at value and impact and discusses policymaking and issues for the future. Conveniently brings together a usable text to which people can easily refer to for an overview of a diffuse areaNo existing book considers this subject area from a UK and European perspectiveAlso aimed at a non-traditional readership including educationalists, lifelong learning activists and those involved with informal learning activities